2015
DOI: 10.1021/acs.langmuir.5b01046
|View full text |Cite
|
Sign up to set email alerts
|

Size and Structure of Clusters Formed by Shear Induced Coagulation: Modeling by Discrete Element Method

Abstract: The coagulation process has a dramatic impact on the properties of dispersions of colloidal particles including the change of optical, rheological, as well as texture properties. We model the behavior of a colloidal dispersion with moderate particle volume fraction, that is, 5 wt %, subjected to high shear rates employing the time-dependent Discrete Element Method (DEM) in three spatial dimensions. The Derjaguin-Landau-Verwey-Overbeek (DLVO) theory was used to model noncontact interparticle interactions, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…The Johnson-Kendall-Roberts (JKR) [24] model for particle-particle adhesion/collision is employed. A number of works available in the literature have used this contact model for simulating aggregation/fragmentation process of particulate aerosol systems [16,17] and, more recently, cluster formation in shear-induced coagulation in a system made by hard spherical particles in water [25,26]. To the best of our knowledge, however, this is the first time that aggregation/breakage phenomena are studied for a system made by a water suspension of hard-gel particles flowing in a microfluidic device.…”
Section: Nomenclaturementioning
confidence: 99%
“…The Johnson-Kendall-Roberts (JKR) [24] model for particle-particle adhesion/collision is employed. A number of works available in the literature have used this contact model for simulating aggregation/fragmentation process of particulate aerosol systems [16,17] and, more recently, cluster formation in shear-induced coagulation in a system made by hard spherical particles in water [25,26]. To the best of our knowledge, however, this is the first time that aggregation/breakage phenomena are studied for a system made by a water suspension of hard-gel particles flowing in a microfluidic device.…”
Section: Nomenclaturementioning
confidence: 99%
“…At moderate volume concentration ( = 0.05), Kroupa et al [37] observed discrepancies with Zaccone approach. The authors explain that for this concentration value, not only rupture but also aggregation will have an impact on equilibrium.…”
Section: Comparison With the Modeling Approaches Proposed In The Litementioning
confidence: 98%
“…The most important feature of this equation is that the scaling exponent p is directly dependent of the structure of the considered aggregate. This theoretical consideration was subsequently used in other works as a comparison basis with results either obtained by experiments [35] or numerical investigations [36,37].…”
Section: Rupturementioning
confidence: 99%
“… 2016 ), and to identify the cluster generation in shear-induced coagulation of microparticles flowing in water (Kroupa et al. 2014 , 2015 ).…”
Section: Introductionmentioning
confidence: 99%